Influence of Buried Pipeline Leakage on the Development of Cavities in the Subgrade - Xianghua Chen; Wenxin Chen; Liyuan Zhao; Yekai Chen (Buildings, 2023)
The rapid pace of urbanization has led to an increasing frequency of road collapses, posing a significant threat to urban traffic safety. Underground pipeline leakage stands out as the primary cause of such collapses. This paper presents a macroscopic analysis of the subgrade seepage erosion process caused by pipeline leakage. Model tests were conducted to investigate the formation mechanism and explore the influence of water level, water flow rate, and soil type. The study revealed that the subgrade seepage erosion caused by pipeline leakage undergoes four distinct stages: infiltration, slow erosion, rapid erosion, and erosion convergence. Soil erosion shares similarities with sand erosion in its developmental process. The water level plays a pivotal role in determining the shape and size of the eroded area caused by sand seepage erosion. The size of the erosion cavities formed during the soil seepage erosion increased along with the increase in the water flow rate. The size of the erosion cavity increased by up to 55.7% when the flow rate was increased by three times. In addition, clay soils do not undergo significant erosional damage but do produce significant settlement. The soil erosion process caused by underground leakages in pipelines was investigated using model tests in this study, which provided valuable information for researchers performing an in-depth analysis of the mechanism of roadbed cavities generated by urban underground pipeline leakage, which is critical for safeguarding people’s travel safety and decreasing social and economic losses.